Translation and validation of Malay version of the simplified diabetic knowledge test - Md Aris, Mohd Aznan; Othman, Umair; Abdul Rahim, Nur Hidayah; Pasi, Hafizah (2018)
Despite improvement in diabetic care, the prevalence of diabetes is still increasing globally. (1) Only a minority of patients were able to achieve their specified glycemic targets. (2) A good level of knowledge is important to empower the patients towards diabetes self-management and further prevention of ill health among them. (3) The simplified diabetes knowledge test (DKT) is a simple knowledge assessment tool, developed for those with low literacy level. (4) This study aimed to translate and validate the Malay version of Simplified Diabetic Knowledge Test questionnaire among diabetic patients attending Klinik Kesihatan Beserah, Kuantan, Pahang, Malaysia